*** DUPLICATE WITH ID NO. 27694 *** Identification and characterization of Enterocytozoon bieneusi isolates from the Proto-Malay and Senoi tribes in Sungai Lembing, Pahang / Azah Ashikin Azhari - Azhari, Azah Ashikin (2016)
Enterocytozoon bieneusi is most common of microsporidian species that infects many types of cells including human and animals. These organisms are causing long lasting diarrhea primarily in immunocompromised patients but microsporidiosis is also higher in immunocompetent individuals. The previous study of microsporidial infection is mostly focused on immunodeficiency or immunosuppressive individuals. Information regarding microsporidial infections among immunocompetent individuals is lacking. Hence, this cross sectional study was carried out to determine prevalence of E. bieneusi infection and to find out the occurrence of E. bieneusi according to age group and gender among the Proto-Malay and Senoi tribes in Sungai Lembing, Pahang, Malaysia. Stool samples were collected from 209 voluntary participants; 96 males and 113 females that aged between one to 85 years old. Demographic data, socioeconomic, environmental, and behavioral information was collected by using pre-tested questionnaire. Overall prevalence of E. bieneusi infection was 3.83 % (8/209). From the observation, majority of individual infected with E. bieneusi was male (8.33 %) can be observed in those aged ≥15 years old. These samples were detected Small Subunit rDNA gene by using Polymerase chain reaction amplification with specific primer EBIEF1 and EBIER1, as demonstrated by an amplicon of 607-bp. This is the first report of E. bieneusi in Malaysia. It is hoped that these findings will allow greater emphasis from public health authorities through public education on personal hygiene and the consumption of boiled or filtered water in order to reduce the infection.